2014
DOI: 10.1186/1476-511x-13-1
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and tolerability of adding coenzyme A 400 U/d capsule to stable statin therapy for the treatment of patients with mixed dyslipidemia: an 8-week, multicenter, double-Blind, randomized, placebo-controlled study

Abstract: BackgroundPatients with mixed hyperlipidemia usually are in need of combination therapy to achieve low-density lipoprotein cholesterol (LDL-C) and triglyceride (TG) target values for reduction of cardiovascular risk. This study investigated the efficacy and safety of adding a new hypolipidemic agent, coenzyme A (CoA) to stable statin therapy in patients with mixed hyperlipidemia.MethodsIn this multi-center, 8-week, double-blind study, adults who had received ≥8 weeks of stable statin therapy and had hypertrigl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
59
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(64 citation statements)
references
References 30 publications
4
59
1
Order By: Relevance
“…Even among those patients who were on lipid lowering agents, the prevalence of those who achieved the desired lipid level was low. A study in China reported that only 23% of patients with dyslipidaemia received treatment and only 17% achieved the desired lipid level of control 7. Another study among Hispanic/Latinos in the USA also reported only 29.5% patients with dyslipidaemia were receiving lipid lowering treatment 8.…”
Section: Introductionmentioning
confidence: 99%
“…Even among those patients who were on lipid lowering agents, the prevalence of those who achieved the desired lipid level was low. A study in China reported that only 23% of patients with dyslipidaemia received treatment and only 17% achieved the desired lipid level of control 7. Another study among Hispanic/Latinos in the USA also reported only 29.5% patients with dyslipidaemia were receiving lipid lowering treatment 8.…”
Section: Introductionmentioning
confidence: 99%
“…The limit of detection was found to be 50 ng·mL −1 based on a signal-to-noise ratio of three, with a correlation coefficient of 0.957. High sensitivity CRP (hs-CRP) of <1000 ng·mL −1 is well known as a reliable biomarker in obesity, metabolic syndrome, and diabetes, thus it is critical to know the concentration level as a risk factor [ 23 ]. Therefore, good quantification in the range of 50–1000 ng·mL −1 allows for a meaningful result from the viewpoint of sensor devices in clinical diagnoses.…”
Section: Resultsmentioning
confidence: 99%
“…It is a hydrolysis product of phosphatidylcholine (PC) in oxLDL(12). In vertebrate plasma, increased levels of LysoPC have been found in atherosclerotic vascular tissue.…”
Section: Introductionmentioning
confidence: 99%